2000
DOI: 10.1161/01.str.31.11.2692
|View full text |Cite
|
Sign up to set email alerts
|

99m Tc Annexin V Imaging of Neonatal Hypoxic Brain Injury

Abstract: Background and Purpose: -Delayed cell loss in neonates after cerebral hypoxic-ischemic injury (HII) is believed to be a major cause of cerebral palsy. In this study, we used radiolabeled annexin V, a marker of delayed cell loss (apoptosis), to image neonatal rabbits suffering from HII. Methods-Twenty-two neonatal New Zealand White rabbits had ligation of the right common carotid artery with reduction of inspired oxygen concentration to induce HII. Experimental animals (nϭ17) were exposed to hypoxia until an ip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…We previously showed that 99m Tc-labeled annexin V uptake correlated with neuronal apoptosis after a stroke (9,10). In this study we have extended our period of observation to 30 d after a stroke and have further defined the cell types that bind annexin V. Our data have shown that there is a shift in the proportion of annexin V2binding cells from predominately neurons at 24 h to microglial cells 7 d after a stroke.…”
Section: Discussionmentioning
confidence: 62%
“…We previously showed that 99m Tc-labeled annexin V uptake correlated with neuronal apoptosis after a stroke (9,10). In this study we have extended our period of observation to 30 d after a stroke and have further defined the cell types that bind annexin V. Our data have shown that there is a shift in the proportion of annexin V2binding cells from predominately neurons at 24 h to microglial cells 7 d after a stroke.…”
Section: Discussionmentioning
confidence: 62%
“…Studies on animal models of neonatal stroke have shown that after large unilateral neonatal hypoxic brain injury, apoptotic processes are present in both hemispheres. 26 No difference in side of brain damage was observed between children with early or delayed diagnosis of perinatal stroke.…”
Section: Discussionmentioning
confidence: 96%
“…Although annexin V is a relatively large protein (about half the molecular weight of albumin), it was shown early on that the protein can be internalized at sites of ischemic injury both in the heart and in the brain and cross the intact blood-brain barrier (39). The transport of exogenously administered annexin V, a protein normally found almost exclusively within cells, also must occur across a protein gradient, suggesting the existence of an energydependent pump mechanism.…”
Section: Physiology Of Annexin V Binding and Internalizationmentioning
confidence: 99%